Low Complexity Algorithm for Multi-path Video Streaming - Elgabli, Anis; Aggarwal, Vaneet; Liu, Ke (International Conference on Signal Processing and Communications, 2018)
In this paper, we propose a multi-path (e.g., WiFi, and LTE) video streaming algorithm for videos encoded using Scalable Video Coding (SVC) in which each chunk of the video is encoded into a single base layer and multiple enhancement layers. The multi-path SVC streaming subject to the available bandwidth of the different paths and the chunk deadlines is formulated as a non convex optimization problem. The objective is to optimize a Quality of Experience (QoE) metric that maintains a tradeoff between maximizing the average quality and minimizing the rebuffering duration and quality switching rate. A novel polynomial time complexity algorithm is developed to solve the proposed non convex optimization problem. Extensive emulated experiments with real SVC encoded videos and real bandwidth traces of public dataset reveal the robustness of our scheme and show its significant performance improvement compared to other multi-path algorithms.